Austria : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents a Detailed Assessment Report on Antimoney Laundering (AML) and Combating the Financing of Terrorism (CFT) for Austria. The authorities have designed and are implementing a comprehensive AML/CFT system, supported by well-developed federal administrative and supervisory bodies, and active professional organizations. The supervisory system for financial institutions is generally sound and efficient. Licensing requirements and the regime of sanctions need to be strengthened, and additional resources should be allocated to supervisory bodies.